Search for a narrow baryonic state decaying to pKS0 and p[bar]KS0 in deep inelastic scattering at HERA - Abramowicz, Halina; Lisovyi, Mykhailo (Physics letters, 2016)
A search for a narrow baryonic state in the pKS0 and p‾KS0 system has been performed in ep collisions at HERA with the ZEUS detector using an integrated luminosity of 358pb−1 taken in 2003-2007. The search was performed with deep inelastic scattering events at an ep centre-of-mass energy of 318GeV for exchanged photon virtuality, Q2, between 20 and 100GeV2. Contrary to evidence presented for such a state around 1.52 GeV in a previous ZEUS analysis using a sample of 121 pb−1 taken in 1996-2000, no resonance peak was found in the p(p‾)KS0 invariant-mass distribution in the range 1.45-1.7 GeV. Upper limits on the production cross section are set.